2015
DOI: 10.1089/zeb.2015.1151
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of DNA Replication Dynamics in Zebrafish Cells

Abstract: Spatiotemporal regulation of DNA replication in the S-phase nucleus has been extensively studied in mammalian cells because it is tightly coupled with the regulation of other nuclear processes such as transcription. However, little is known about the replication dynamics in nonmammalian cells. Here, we analyzed the DNA replication processes of zebrafish (Danio rerio) cells through the direct visualization of replicating DNA in the nucleus and on DNA fiber molecules isolated from the nucleus. We found that zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…When the pre-MBT embryos (15 min Sphase) were compared to ZTF cells (8 h S-phase), the pre-MBT timing profile appeared compressed and resembled random data ( Fig. 4A; Kane and Kimmel 1993;Kuriya et al 2015). However, consistent timing profiles between biological replicates were evident when the data were scaled to normalized units (Fig.…”
Section: A Pre-mbt Replication Timing Program Anticipates Initial Zygmentioning
confidence: 80%
“…When the pre-MBT embryos (15 min Sphase) were compared to ZTF cells (8 h S-phase), the pre-MBT timing profile appeared compressed and resembled random data ( Fig. 4A; Kane and Kimmel 1993;Kuriya et al 2015). However, consistent timing profiles between biological replicates were evident when the data were scaled to normalized units (Fig.…”
Section: A Pre-mbt Replication Timing Program Anticipates Initial Zygmentioning
confidence: 80%
“…1(C)). Although the temporal order of these patterns was determined from our previous study, 9) the frequency of pattern II was particularly high, which was also observed in somatic cells. Similar results were obtained when we used embryos at 2.75-4 hpf (blastula stage) where cell division takes between 15 and 54 min.…”
mentioning
confidence: 76%
“…DNA fibers from EdU-labeled cells were prepared as described previously. 9) A fluorescence microscope (Axioplan 2 MOT; Carl Zeiss, Inc. Jena, Germany) equipped with a 63×objective lens and an ORCA R2 camera (Hamamatsu; Shizuoka, Japan) was used for imaging. This experimental system allows us to collect single embryo-derived cells, thus enabling analysis of the dynamic nature of DNA replication within a single embryo.…”
mentioning
confidence: 99%
“…The DNA fiber assay was performed as described ( Conti et al, 2007 ; Kuriya et al, 2015 ; Michalet et al, 1997 ). Briefly, cells were labeled with 100 µM of IdU or CldU for 30 min and harvested by trypsinization.…”
Section: Methodsmentioning
confidence: 99%